Anticoagulant counter ion impact on bioanalytical LC–MS/MS assays: results from discussions and experiments within the European Bioanalysis Forum. (November 2011) - Sennbro, Carl Johan; Knutsson, Magnus; van Amsterdam, Peter; Timmerman, Philip
Background: In regulated bioanalysis, the need for partial validation when changing the counter ion of the anticoagulant is currently being debated within the bioanalytical community. To date, industry and the health authorities have not yet reached a consensus on this issue. The aim of the present study was to evaluate the impact of a change in counter ion when using the same anticoagulant on LC–MS/MS assay performance for a broad array of new chemical entities, compiling data generated at companies within the European Bioanalysis Forum (EBF).Results: In all, 15 EBF member companies provided experimental data on partial validation. In total, data from 42 LC–MS/MS assays were evaluated. The results show that a change in counter ion when using the same anticoagulant had no impact on assay performance.Conclusion: Based on these results and on conclusions from previous studies, the EBF recommends that in regulated bioanalysis, plasma samples containing different counter ions, but the same anticoagulant, should be regarded as equal matrices, thus removing any need for partial validation.